More than money? An empirical investigation of socio-psychological drivers of financial citizen participation in the German energy transition - Dominik L. Schall (Cogent Economics & Finance, 2020)
While financial citizen participation plays an increasing role in renewable energy, there is a lack of understanding which socio-psychological factors correlate with a decision to privately invest in renewable energy. Based on a conceptual model and an extensive literature review, a survey among retail investors of renewable energy projects in Germany was conducted and compared to existing population samples using logistic regressions and factor analysis. This research finds that the typical retail investor in renewable energy in Germany is more likely to be male with a higher income, to have a higher education, and to live in a more rural area compared with the overall population. The typical investor exhibits strong proenvironmental beliefs and behaviors as well as a predisposition for active citizenship. Furthermore, getting a form of non-financial or 'psychic return' from the investment seems to be important for the investment decision. Strategic adaptions for public and private actors to increase retail investment in renewable energy are discussed.
Keywords: 330; energy transition; renewable energy; socio-psychological factors; citizenparticipation; behavioral finance; investment decisions